Molecular basis of RNA polymerase promoter specificity switch revealed through studies of Thermus bacteriophage transcription regulator - Severinov, Konstantin (Landes Bioscience, 2014)
Transcription initiation is the central point of gene expression regulation. Understanding of molecular mechanism of transcription regulation requires, ultimately, the structural understanding of consequences of transcription factors binding to DNA-dependent RNA polymerase (RNAP), the enzyme of transcription. We recently determined a structure of a complex between transcription factor gp39 encoded by a Thermus bacteriophage and Thermus RNAP holoenzyme. In this addendum to the original publication, we highlight structural insights that explain the ability of gp39 to act as an RNAP specificity switch which inhibits transcription initiation from a major class of bacterial promoters, while allowing transcription from a minor promoter class to continue.